Subjectivities interwoven in records of gender violence and migration processes: Liminal transformation thresholds - Pilar Albertín Carbó; Universidad de Girona (Escuela de Psicología, Pontificia Universidad Católica de Valparaíso, 2016)
A diversity of daily life processes are responsible for the build-up of subjectivity, some of them take place under critical circumstances, as is the case with gender violence instances that intersect with migration processes to foreign countries. This work attempts to look into the transformation of subjectivites that emerge from those critical instances, and to show how those subjectivities may be “seized” from the utterances (five of them) of migrant women about their experiences. Our results indicate that they are subjective accounts which are vulnerable to start with and which are subject to hegemonic and constrictive expository positions. Upon liminal experiences such as pain, discomfort, or else receiving assistance by others, and future expectations, those accounts turn into emerging subjectivities that we validate as having significant transformative power.